(AI)2: Artificial Intelligence on Assessment and Instruction - Darwin M. Andres; Romellen G. Ramos (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study intended to assess the extent of knowledge, skills, and attitudes of the Nueva Ecija University of Science and Technology - College of Education faculty members in utilizing artificial intelligence in their instruction and assessment using descriptive-correlational research design. Specifically, this study described the profile of the faculty in terms of age, educational attainment, years of service, and number of relevant training in Artificial Intelligence (AI). Moreover, it aimed to determine the degree of knowledge, skills, and attitudes of the respondents in using AI and to identify which profile variable has a significant relationship on their knowledge, skills, and attitudes in using AI. The results show that the majority of the respondents have Doctorate units. Half of the respondents have been teaching for more than 16 years but most of the respondents have less than five relevant training /seminars about AI while the largest percentage of the population aged below 30 years old. More so, as to their knowledge, skills, and attitudes in using the AI platforms both in instructions and assessments, the respondents have moderate awareness and low competencies but have high willingness. Meanwhile, this study significantly found out that in using AI: the younger the teachers are, the more competent and willing they are; the shorter years that the teachers are in the service, the more competent they are; and as the number of AI relevant trainings attended by the respondents increases, the more they become aware on the use of AI, the higher their competencies become, and the more they develop willingness to learn AI. Lastly, the researchers advise the future researchers to separately test the knowledge, skills, and attitudes of the teachers in terms of instruction and assessment.